EKSISTENSI PEREMPUAN DALAM NOVEL CINTA 2 KODI KARYA ASMA NADIA: KAJIN KRITIK SASTRA FEMINISME POSTKOLONIAL BERDASARKAN PERSPEKTIF ANIA LOOMBA - Ilmia, Miftahul (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
Feminism fights for two things that women in general have not been able to have, namely their equality with men and their right to determine what is good for them. In the novel “Cinta 2 Kodi”, this can be seen from one of the female characters, namely Kartika. The Kartika character in this novel is described as a brave and intelligent woman. Kartika as the main character has proven that people who can create success are not only men, women can also create success using their own methods. From this it can be seen that the existence of women during the colonial period was still there, not only fixated on men, but women at this time also played an important role in all matters. Women can be equal to men if they are willing to try. Postcolonial feminism can also be seen from the many problems regarding patriarchal culture that are even experienced by all the female characters in Asma Nadia's Cinta 2 Kodi novel. In this novel there is a woman's misery that can be seen through the characters Kartika and Aryani who both have a patient, gentle character and depict a strong woman who is able to resist oppression and take action to defend herself. Kartika's character was able to become a feminist figure who was patient and strong in going through the various difficulties she experienced at the time when her application with Farid had to be canceled due to the feud between her parents. This was what the women of the colonial period had to do to be patient and strong in dealing with problems.